Warming exacerbates the impact of nutrient enrichment on microbial functional potentials important to the nutrient cycling in shallow lake mesocosms. Issue 6 (24th April 2021) - Ren, Lijuan; Liu, Yuanyuan; Lauridsen, Torben L.; Søndergaard, Martin; Han, Boping; Wang, Jianjun; Jeppesen, Erik; Zhou, Jizhong; Wu, Qinglong L.
Abstract: Shallow lakes, the most numerous waterbodies on Earth, are susceptible to climate warming and nutrient enrichment whose effects on the microbial functional potentials are not yet fully understood, however. Here, we applied a microarray‐based technology termed GeoChip 5.0 to investigate microbial functional genes at the beginning of April in shallow lake ecosystems simulated in mesocosms that have been undergoing nutrient enrichment and warming for 9 yr. Our results showed that warming exacerbated the impact of nutrient enrichment on microbial metabolic potentials and significantly elevated the microbial autotrophy potentials, carbon degradation potentials (e.g., starch, hemicellulose, cellulose, and chitin), and polyphosphate mobilization potentials. We also observed that warming enhanced the impacts of nutrient enrichment on microbial functional gene structure. The combination of warming and nutrient enrichment increased the deterministic effect from phytoplankton, causing higher interlinking of microbial functional genes involved in the carbon, nitrogen, phosphorus, and sulfur cycling in correlation‐based networks. Overall, we propose that the joint effect of warming and nutrient enrichment promoted the autotrophic carbon supply and the heterotrophic carbon demand and changed the carbon fluxes in the experimental mesocosms.